Optimization, characterization and immobilization of alkaline protease from chicken feather and fish fin using mixed culture - Thanoon, Raid Duraid (2018)
Environmental pollution is a major problem in the developed and developing countries. Fish fins (FF) and chicken feathers (CF) can be sources of solid waste contamination; hence, both were investigated for alkaline protease (AP) production through microbial degradation. This study aims to extract and produce keratin and collagen from animal waste by the action of mixed culture bacteria and degrade the selected proteins to produce alkaline protease enzyme. The study further aims to immobilize the produced enzymes for industrial application. In this study, proteins were extracted from wastes and added to M9 minimal salt production medium containing the bacterial suspension and assayed for AP production. The process parameters were optimized via One-Factor-at-a-Time (OFAT) and the optimum conditions for CF and FF were determined as pH 9.0, the temperature of 28°C for CF and 40°C for FF, and an incubation period of 6 and 10 days, respectively. The optimum carbon source was determined as galactose and glucose while the optimum nitrogen source was ammonium chloride and beef extract for CF and FF, respectively. Inoculum size was found to be 1.5 mL for both samples, while a protein volume of 1.5 and 2.0 mL for CF and FF respectively, was recorded. The protein was partially purified using ammonium sulphate precipitation in 1L optimum parameters for each waste. Protein content was assayed and determined as 1.183 ± 0.035 and 0.852 ± 0.050 mg/ml respectively, for CF and FF while enzyme activity was determined as 0.254 ± 0.001 and 0.246 ± 0.014 U/ml respectively, for CF and FF. After dialysis, there was 1.235 and 2.110 folds increase in the enzyme activities of CF and FF respectively. The proteins were digested and the peptides were sequenced using LC-MS. From the LC-MS report, there were 2 and 4 out of 11 and 59 matched and identified peptides for CF and FF, respectively. Enzyme immobilization was performed in sodium alginate using 1.3 and 0.688g of the free enzyme solution to form beads. The activity of the enzymes immobilized in 0.25g beads was 0.398 and 0.411 (U/ml) for CF and FF-derived enzymes, respectively. The reusability of the immobilized enzymes in protein degradation was assayed for 4 protein degradation cycles. The liberated protein content after the 4th cycle was found to be 0.232 ± 0.001 and 0.238 ± 0.006 mg/ml for CF and FF-derived enzymes, respectively. After the 4th cycle, a gradual decrease in activity (approximately 10% activity loss) was noticed as the obtained protein contents decreased by up to 40% (0.168 ± 0.002 and 0.152 ± 0.003 mg/ml) for the CF and FF-derived proteins, respectively. The storage stability of the immobilized beads was determined by maintaining the immobilized enzymes via crosslinking and simple adsorption at 4oC for 5 days. The immobilized enzymes were also checked for blood stain removal (a test to check for its potential as a detergent additive) and found to remove blood stains from a piece of cloth after 6 different treatments within 60 min at room temperature. It can be concluded that both the crude and immobilized AP enzymes can be industrially used as detergent additives.